2016
DOI: 10.1093/icb/icw030
|View full text |Cite
|
Sign up to set email alerts
|

Migratory monarchs wintering in California experience low infection risk compared to monarchs breeding year-round on non-native milkweed

Abstract: Long-distance migration can lower infection risk for animal populations by removing infected individuals during strenuous journeys, spatially separating susceptible age classes, or allowing migrants to periodically escape from contaminated habitats. Many seasonal migrations are changing due to human activities including climate change and habitat alteration. Moreover, for some migratory populations, sedentary behaviors are becoming more common as migrants abandon or shorten their journeys in response to supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 85 publications
3
55
0
Order By: Relevance
“…In some locations, infection prevalence reached 100%, and volunteer reports showed that monarch winter-breeding occurs exclusively at sites with tropical milkweed. A strikingly similar pattern was observed in the western USA: Resident monarchs breeding year-round in southern California face nine-times higher infection risk compared with migratory monarchs at coastal overwintering sites [46]. High infection prevalence has been attributed to the loss of both migratory escape and culling.…”
Section: Monarch Butterflies and Their Debilitatingsupporting
confidence: 54%
See 1 more Smart Citation
“…In some locations, infection prevalence reached 100%, and volunteer reports showed that monarch winter-breeding occurs exclusively at sites with tropical milkweed. A strikingly similar pattern was observed in the western USA: Resident monarchs breeding year-round in southern California face nine-times higher infection risk compared with migratory monarchs at coastal overwintering sites [46]. High infection prevalence has been attributed to the loss of both migratory escape and culling.…”
Section: Monarch Butterflies and Their Debilitatingsupporting
confidence: 54%
“…One of the most popular milkweed in gardens is a non-native species, tropical milkweed (A. curassavica; figure 3), which is attractive, easy to grow and commonly sold in nurseries [47,154]. Unlike most native milkweeds that enter dormancy in the autumn, tropical milkweed persists throughout the year in mild climates [23,46,47]. Tropical milkweed also has high concentrations of secondary compounds called cardenolides that are attractive to monarchs, provide a defence against many predators, and prolong lifespan for infected individuals [155][156][157].…”
Section: Monarch Butterflies and Their Debilitatingmentioning
confidence: 99%
“…At the same time, monarchs may breed throughout the winter on introduced host plants now grown year-round near the Gulf of Mexico (Satterfield et al, 2015). Year-round breeding has been hypothesized to lead to an increase of parasites (Satterfield et al, 2016), shed as spores by adults on food plants, which are subsequently ingested by larvae causing infection. Heavily infected monarchs are less likely to survive during fall migration (Bartel et al, 2011), which suggests butterflies born in the southwest and southeast regions suffer higher mortality during the migration to Mexico in years with higher regional parasite levels (Satterfield et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that infection prevalence increases in monarch butterflies over the breeding season (in this study and in Bartel et al ., ) and is highest in year‐round breeding monarchs (Altizer et al ., ; Satterfield et al ., ) suggests consequences for monarch host–parasite dynamics under global environmental change. Anthropogenic habitat changes due to the planting of non‐native milkweed plants in Texas and along the Gulf Coast may result in a longer breeding season and high infection prevalence among monarchs at these sites (Satterfield et al ., ).…”
Section: Discussionmentioning
confidence: 99%